Immunogenicity of a protective intradermal DNA vaccine against lassa virus in cynomolgus macaques - Jingjing Jiang; Preeti Banglore; Kathleen A. Cashman; Connie S. Schmaljohn; Katherine Schultheis; Holly Pugh; Jacklyn Nguyen; Laurent M. Humeau; Kate E. Broderick; Stephanie J. Ramos (Human Vaccines & Immunotherapeutics, 2019)
Lassa virus (LASV) is a hemorrhagic fever virus of the Arenaviridae family with high rates of mortality and co-morbidities, including chronic seizures and permanent bilateral or unilateral deafness. LASV is endemic in West Africa and Lassa fever accounts for 10–16% of hospitalizations annually in parts of Sierra Leone and Liberia according to the CDC. An ongoing outbreak in Nigeria has resulted in 144 deaths in 568 cases confirmed as LASV as of November 2018, with many more suspected, highlighting the urgent need for a vaccine to prevent this severe disease. We previously reported on a DNA vaccine encoding a codon-optimized LASV glycoprotein precursor gene, pLASV-GPC, which completely protects Guinea pigs and nonhuman primates (NHPs) against viremia, clinical disease, and death following lethal LASV challenge. Herein we report on the immunogenicity profile of the LASV DNA vaccine in protected NHPs. Antigen-specific binding antibodies were generated in 100% (6/6) NHPs after two immunizations with pLASV-GPC. These antibodies bound predominantly to the assembled LASV glycoprotein complex and had robust neutralizing activity in a pseudovirus assay. pLASV-GPC DNA-immunized NHPs (5/6) also developed T cell responses as measured by IFNγ ELISpot assay. These results revealed that the pLASV-GPC DNA vaccine is capable of generating functional, LASV-specific T cell and antibody responses, and the assays developed in this study will provide a framework to identify correlates of protection and characterize immune responses in future clinical trials.